2002
DOI: 10.30843/nzpp.2002.55.3941
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phylloplane microorganism populations in Canterbury apple orchards

Abstract: Micro-organism populations on the leaf surface can be an indicator of environmental health in orchards. A method was developed to detect changes in these populations in apple orchards. Firstly, the variation within orchards was investigated by sampling leaves from seven locations within four trees in spring and autumn. The population density and species richness of micro-organisms when grown on PDA showed tree and season effects (P<0.05) but few significant effects of locations within trees or of replicated br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
1
2
0
2
Order By: Relevance
“…An overall higher abundance and diversity of micro-organisms was observed in organic orchards across all sites during spring and autumn, compared with that observed for IFP orchards. A comparable result was also reported for micro-organism populations over spring in Canterbury orchards in a linked study (Bakker et al 2002), which further validates both methodology and some of the observations reported here. Despite lower population richness in IFP orchards, both studies do show some recovery of richness in Canterbury and Hawke's Bay orchards by autumn.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An overall higher abundance and diversity of micro-organisms was observed in organic orchards across all sites during spring and autumn, compared with that observed for IFP orchards. A comparable result was also reported for micro-organism populations over spring in Canterbury orchards in a linked study (Bakker et al 2002), which further validates both methodology and some of the observations reported here. Despite lower population richness in IFP orchards, both studies do show some recovery of richness in Canterbury and Hawke's Bay orchards by autumn.…”
Section: Discussionsupporting
confidence: 90%
“…Following incubation, microbial colony forming units (CFUs) were enumerated and classified into four main groups: bacteria, smooth yeasts, hyphal yeasts and filamentous fungi. The organisms in each group were further classified into Recognisable Taxonomic Units (RTUs) based on different colony growth patterns and phenotypic morphologies (Bakker et al 2002). The population abundance (CFUs/leaf) and the species richness (RTUs/leaf) were determined after 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Isolates were selected from the eight main morphological yeast RTU as determined in earlier research (Bakker et al 2002;Waipara et al 2002). However, special emphasis was given to isolates of Aureobasidum pullulans (a yeast-like fungus henceforth referred to as a yeast), which is commonly found in New Zealand apple orchards (Pennycook & Newhook 1981;Waipara et al 2002), and is shown to suppress postharvest diseases (Castoria et al 2001;Ippolito et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…У грибов, обитающих на поверхности листьев растений, наблюдаются разные пики разнообразия в течение года, что в первую очередь связано с сезонными изменениями климата, а также доступностью органических веществ [11,14,32,40]. Явления смены видового состава грибов филлопланы в течение года (сезонные сукцессии) изучены в разных экологических условиях [17,19,36].…”
Section: Introductionunclassified
“…Они слабо изучены относительно других групп грибов, например патогенных, которые развиваются в тканях листа [1,2,11,32]. По мнению ряда авторов, микромицеты филлопланы не наносят вреда растению [14,27]. Они обитают преимущественно на верхней поверхности листьев, хотя иногда способны развиваться и на нижней стороне листовой пластинки [35].…”
Section: Introductionunclassified